PROGRAM KAMPUS MENGAJAR 7: EFEKTIFKAH TERHADAP KEMAMPUAN NUMERASI SISWA DI SDN KERTASARI? - Adinda Ayuning Zahirah; Mita Putri Sindiawati; Zalfa Mufidah; Sendi Fauzi Giwangsa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to examine the effectiveness of the Kampus Mengajar 7 Program on the numeracy skills of fifth-grade students at SDN Kertasari. The research employs a quantitative approach with an ex post facto design, involving 24 students as the sample. The instruments used were pre-test and post-test assessments, with data analyzed using the Wilcoxon test and effect size measurement. The results indicate a significant improvement in students' numeracy skills after participating in the program. The average score increased from 33.75 (pre-test) to 47.71 (post-test), with the Wilcoxon test result (p = 0.003) showing a significant difference and an effect size of 0.608, indicating a large effect. These findings confirm that the Kampus Mengajar Program can serve as a strategic intervention to enhance numeracy skills among elementary school students.